Temporal Coarse-Graining in a Slip Link Model for Polydisperse Polymer Melts - Shanbhag, Sachin (Frontiers in Physics, 2020)
For ecoSLM -an ultra coarse-grained slip link model -the ability to use a time-step that increases with chain molecular weight is an important source of efficiency in modeling the linear rheology of monodisperse chains. This feature is labeled "temporal coarse-graining" in this paper. It is compromised for blends of linear chains, where the time-step is set by the short chains, but the length of the simulation run is determined by the long chains. The problem is present for any polydisperse sample, and is particularly acute for binary blends with widely separated molecular weights. To recover temporal coarse-graining, we propose an adaptive time-step algorithm, where the time-step is determined by the shortest unrelaxed chains in the ensemble, which increases as the simulation proceeds. It involves two additional steps: recalibration, which is triggered when any component relaxes completely, and re-equilibration, in which slip links on completely relaxed components are renewed. We obtain reasonable settings for these steps, and validate the the adaptive time-step algorithm by comparing it with the original, constant time-step ecoSLM for binary, ternary, and polydisperse blends. Speedups ranging from 50% to 1500% are obtained when molecular weights of the components are widely separated, without a significant loss of accuracy. Conversely, the adaptive time-step algorithm is not recommended when molecular weights are not well-separated, since it can be slower than the constant time-step method.